What is love? Precarious lives, precarious loves in the works of Italian women graphic novelists - Mandolini, Nicoletta (2022)
After several years of an almost exclusively male presence, the Italian graphic novel scene has finally opened to a multitude of creative female voices gaining a certain popularity and critical success, with multi-faceted works spanning from autobiographical themes to graphic science and beyond. Inevitably conditioned by the existential precarity of the context in which they live and work, their production reflects on their sentimental and sexual lives, both staging new, fluid relationships (Bauman 2003; Penny 2014), and trying to find an alternative perspective to the much discussed issue of the male gaze (Mulvey 1975). Most notable examples are Rita Petruccioli (Ti chiamo domani, 2019), Cristina Portolano (Non so chi sei, 2017) and Flavia Biondi (La giusta mezura 2017). This contribution aims to discuss the role played by women graphic novelists in portraying the gendered dimension of emotional precarity (Butler 2009) in an historical period (the 2000s) and a societal context (Italy) in which pervasive financial, geographical and identity insecurities, coupled with a persistent sexist culture, force female subjectivities to deconstruct both the patriarchal grand narrative of romantic love and the radical feminist myth of sexual liberation. Adopting a theoretical framework that puts together reflections of gender and sentimental precarity (Bauman 2003; Morini 2010; Putino 2011; Witt 2016; Berardi 2017; Illouz 2017), the chapter investigates the creative strategies adopted to represent the challenges as well as the opportunities that flexibility poses to female relationality and desire.